ASEAN Orthopaedic Association Education Committee - Orthopaedic curriculum for residency training 2019 - Choon, David; Canete, Arturo C.; Leung, Jean Pierre F.; Kritsaneephaiboon, Apipop; Maung, Mg Htwe; A. Mokhtar, Sabarul; Tobing, Dohar; Myint, Thaung; Lee, Peter; Yeo, Sing Jin; Khalid, Kamarul Ariffin; Khin, Mg Myint; et al. (ASEAN Orthopaedic Association, 2019)
In November 2013, Dr Dohar Tobing, who was the President of the ASEAN Orthopaedic Association at that time, organized a Seminar on Orthopaedic Education in Yogyakarta to discuss residency training in ASEAN. At this initial meeting the training program in each country was presented by representatives from each ASEAN country. Subsequently the ASEAN Orthopaedic Association established the Education Committee under the chairmanship of Professor Lee Eng Hin to develop a common syllabus/curriculum for all ASEAN countries based on minimum standards required to practice competently as a general orthopaedic surgeon. The main objective of having a common curriculum is to facilitate exchanges of residents and fellows amongst the ASEAN countries to increase their exposure to orthopaedic conditions in the region and improve their breadth and depth of knowledge and skills. The first meeting of the Education Committee was held in Cebu in November 2014 and the Committee has since met twice a year in May and November. Training programs in the ASEAN countries were discussed and a consensus was reached on the structure and length of the training program for the AOA curriculum. In May 2016, three workgroups were formed under the leadership of Professor David Choon, Dr Dohar Tobing and Professor Lee Eng Hin to develop the detailed curriculum in the following areas: a) General Orthopaedics/Trauma/Infection/Sports/Pathophysiology/Basic Science Lead: David Choon Members: Arturo C. Canete, Jean Pierre F. Leung, Apipop Kritsaneephaiboon, Maung Mg Htwe, Sabarul A. Mokhtar b) Adult Orthopaedics/Spine/Upper Limb/Foot & Ankle/Biomaterials/Biomechanics Lead: Dohar Tobing Members: Myint Thaung, Peter Lee, Yeo Sing Jin, Kamarul Ariffin Khalid, Khin Mg Myint, Azlina Abbas c) Pediatrics/Oncology Lead: Lee Eng Hin Members: Edward HM Wang, Kanyika Chamniprasas, Pornchai Mulpruek, Istan Irmansyah Irsan, Abdul Razak Sulaiman, Wan Faisham Nu’man Wan Ismail In addition to their contributions as workgroup members, the following individuals made substantial contributions in the following areas:  Pathophysiology/Basic Science: Vivek Ajit Singh and David Choon  General Ortho: Wan Faisham Nu’man Wan Ismail and Kamarul Ariffin Khalid  Trauma: Arturo Cañete and Jean Pierre Leung  Sports Medicine: Aung Myo Win  Adult-Hip & Knee: Maung Mg Htwe and Myint Thaung  Spine: Dohar Tobing  Upper limb/Hand: Khin Mg Myint  Foot & Ankle: Inderjeet Singh  Paediatrics: Lee Eng Hin and Abdul Razak Sulaiman  Oncology: Edward Wang and Istan Irmansyah Irsan